Risk of injurious road traffic crash after prescription of antidepressants. (7th October 2012) - Lagarde, E; Queinec, R; Philip, P; Gadegbeku, B; Delorme, B; Moore, N; Suissa, S; Salmi, L -R; Orriols, L; ,
Abstract : Background: Antidepressants are commonly used worldwide. Experimental studies have suggested that antidepressants may impair driving abilities. Aims/Objectives/Purpose: The study aims to estimate the risk of road traffic crash associated with prescription of antidepressants. Methods: Data from three French national databases were extracted and matched: the national health care insurance database, police reports, and the national police database of injurious crashes. A case-control analysis comparing 34 896 responsible versus 37 789 non-responsible drivers was conducted. Case-crossover analysis was performed to investigate the acute effect of medicine exposure. Results/Outcomes: 72 685 drivers identified by their national healthcare number, involved in an injurious crash in France over the July 2005 to May 2008 period, were included. 2936 drivers (4.0%) were exposed to at least one antidepressant on the day of the crash. The results showed a significant association between the risk of being responsible for a crash and prescription of antidepressants (OR=1.34 (1.22 to 1.47)). The case-crossover analysis showed no association with treatment prescription but the risk of road traffic crash increased after an initiation of an antidepressant treatment (OR=1.49 (1.24 to 1.79)) and after a change in antidepressant treatment (OR=1.32 (1.09 to 1.60)). Significance/Contribution to the Field: Patients and prescribers should be warned about the risk of crash during periods of antidepressant medication and particularly high vulnerability periods such as those when a treatment is initiated or modified.